Selective enhancement of attentional networks in college table tennis athletes: a preliminary investigation - Wang, Biye (PeerJ, 2016)
The purpose of the study was to investigate the characteristics of the attentional network in college table tennis athletes. A total of 65 college students categorized as table tennis athlete group or non-athlete group participated in the study. All participants completed the attentional network test (ANT) which measured the alerting, orienting and executive control networks. The results showed a significant difference between the athlete and non-athlete group for executive control network (p < 0.01), while no differences were observed for alerting (p > 0.05) or orienting (p > 0.05) networks. These results combined suggest that college table tennis athletes exhibited selectively enhanced executive control of attentional networks.